Ionic liquid effect: selective aniline oxidative coupling to azoxybenzene by TiO2. Issue 3 (1st December 2014) - Qadir, Muhammad I.; Scholten, Jackson D.; Dupont, Jairton
Abstract : TiO2 promotes the oxidative catalytic coupling of anilines to diazo compounds. In ionic liquids, azoxybenzene is formed in high selectivity, whereas in toluene azobenzene is formed almost exclusively. Abstract : Simple commercially available TiO2 in ionic liquids (ILs) promotes the oxidative catalytic coupling of anilines to diazo compounds. For example, the reaction of aniline with molecular oxygen (5 bars) in the presence of TiO2 and functionalised imidazolium-based ILs affords azoxybenzene in up to 85% selectivity. The catalytic selectivity and activity are mainly related to the viscosity, oxygen solubility, and stability of the superoxide ion (O2 ˙ − ) and ionic species provided by the IL (IL effect). This effect is evident since most of the reactions performed in the presence of ILs gave as major products the azoxybenzene zwitterions. This is in opposition to that performed in toluene, which gave almost exclusively azobenzene.